A Systematic Literature Review on Quality of Service in 5G Cellular Networks: Challenges and Opportunities in the Indonesian Context - Kardiyasa, Komang Agus Putra; Putra, Anak Agung Adi Wiryya; Suprianingsih, Ni Wayan (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2026)
The fifth-generation (5G) network promises ultra-fast connectivity, massive device density, and low latency, yet ensuring reliable Quality of Service (QoS) remains a major challenge. This study conducts a Systematic Literature Review (SLR) of 35 peer-reviewed articles published between 2020–2023, sourced from IEEE Xplore, Scopus, and Google Scholar. The review identifies key QoS mechanisms such as network slicing, resource allocation, and latency management, while challenges persist in scalability, interoperability, and security. Emerging trends highlight the growing role of Artificial Intelligence (AI), Machine Learning (ML), and Software-Defined Networking (SDN) for QoS optimization. In Indonesia, regulatory readiness, spectrum allocation, and uneven infrastructure present both challenges and opportunities. The study contributes by synthesizing recent findings, outlining research gaps, and offering practical insights for policymakers, operators, and researchers.